The Effect of Human Insect Repellents on Perennial Ryegrass (Lolium perenne) Growth and Recovery - J. Hoyle; Peyton E. South (Kansas Agricultural Experiment Station Research Reports, 2017)
Turfgrass damage has been observed from misapplications of human insect repellents. Minimal research has been conducted to determine the cause of the damage. Greenhouse research trials were initiated in November 2016 to survey various human insect repellents on turfgrass growth and recovery. Insect repellents resulted in a wide range of damage. No common trend was observed, although the research trial shows possible repellents to be used around turfgrass that will minimize turfgrass injury.
Keywords: insect repellents; perennial ryegrass; turfgrass injury